Detection and Physicochemical Characterization of Membrane Vesicles (MVs) of Lactobacillus reuteri DSM 17938 - Grande, Rossella; Celia, Christian; Mincione, Gabriella; Stringaro, Annarita; Di Marzio, Luisa; Colone, Marisa; Di Marcantonio, Maria C.; Savino, Luca; Puca, Valentina; Santoliquido, Roberto; Locatelli, Marcello; Muraro, Raffaella; et al. (Frontiers in Microbiology, 2017)
Membrane vesicles (MVs) are bilayer structures which bleb from bacteria, and are important in trafficking biomolecules to other bacteria or host cells. There are few data about MVs produced by the Gram-positive commensal – derived probiotic Lactobacillus reuteri; however, MVs from this species may have potential therapeutic benefit. The aim of this study was to detect and characterize MVs produced from biofilm (bMVs), and planktonic (pMVs) phenotypes of L. reuteri DSM 17938. MVs were analyzed for structure and physicochemical characterization by Scanning Electron Microscope (SEM) and Dynamic Light Scattering (DLS). Their composition was interrogated using various digestive enzyme treatments and subsequent Transmission Electron Microscopy (TEM) analysis. eDNA (extracellular DNA) was detected and quantified using PicoGreen. We found that planktonic and biofilm of L. reuteri cultures generated MVs with a broad size distribution. Our data also showed that eDNA was associated with pMVs and bMVs (eMVsDNA). DNase I treatment demonstrated no modifications of MVs, suggesting that an eDNA-MVs complex protected the eMVsDNA. Proteinase K and Phospholipase C treatments modified the structure of MVs, showing that lipids and proteins are important structural components of L. reuteri MVs. The biological composition and the physicochemical characterization of MVs generated by the probiotic Lactobacillus reuteri may represent a starting point for future applications in the development of vesicles-based therapeutic systems.